1999
DOI: 10.1006/brln.1998.2049
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Neighborhood Density on Phonetic Categorization in Aphasia

Abstract: This manuscript bas been reproduced from the microfilm master. UMI films the text directIy trom the original or copy submittOO. Thus, sorne thesis and dissertation copies are in typewriter face, while others May be from any type of computer printer.The quality of tbis reproduction is dependent upon tbe quality of the copY submitted. Broken or indistinct print, colored or poor quality illustrations and photographs, print bleedthrough, substandard margins, and improper alignment cao adversely affect reproduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 56 publications
(151 reference statements)
5
27
2
Order By: Relevance
“…The results do agree with the Boyczuk and Baum (1999) study, mentioned in the introduction, who also found that neighbourhood density affected performance of the same three groups of participants equally. It must be noted again that their study was not designed to investigate initial lexical activation, but heuristic processes used in phonetic categorization.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The results do agree with the Boyczuk and Baum (1999) study, mentioned in the introduction, who also found that neighbourhood density affected performance of the same three groups of participants equally. It must be noted again that their study was not designed to investigate initial lexical activation, but heuristic processes used in phonetic categorization.…”
Section: Discussionsupporting
confidence: 91%
“…Given that Broca's aphasics showed a heavier reliance on lexical strategies in an earlier study (i.e. a larger lexical effect than controls on a phonetic categorization task; Blumstein, Burton, Baum, Waldstein, and Katz, 1994), Boyczuk and Baum (1999) initially expected a larger neighbourhood density effect for non-fluent aphasics than for fluent aphasics and control participants. Although no significant interactions between density effect and participant group were found, the density effect was numerically largest for the fluent patients.…”
Section: Neighbourhood Density Effects In Aphasic Listeners 197mentioning
confidence: 87%
See 3 more Smart Citations